2001
DOI: 10.1007/s004200100231
|View full text |Cite
|
Sign up to set email alerts
|

Association between blood levels of lead, blood pressure and risk of diabetes and heart disease in workers

Abstract: The study supports the hypothesis of a positive association between lead exposure, high blood pressure and risk of diabetes and heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 16 publications
2
44
1
Order By: Relevance
“…Lead is also considered one of the contributing factors to hypertension (Ghiasvand et al, 2013;Muntner et al, 2003), and blood exposure has been associated with high arterial blood pressure in occupationally exposed workers and in the general population (ATSDR, 2007;Bener et al, 2001;Cheng et al, 2001;Kuno et al, 2013). Participants in our study with moderate elevations of diastolic pressure displayed higher levels of BLL, which is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 94%
“…Lead is also considered one of the contributing factors to hypertension (Ghiasvand et al, 2013;Muntner et al, 2003), and blood exposure has been associated with high arterial blood pressure in occupationally exposed workers and in the general population (ATSDR, 2007;Bener et al, 2001;Cheng et al, 2001;Kuno et al, 2013). Participants in our study with moderate elevations of diastolic pressure displayed higher levels of BLL, which is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 94%
“…These include obesity, hypertension, and other comorbid conditions (10,20). Fourth, environmental conditions, such as dioxin (27,28), lead (29), and polychlorinated biphenyl (30) exposure, may also play a role in the association of adverse neighborhood and housing conditions with development of diabetes.…”
mentioning
confidence: 99%
“…Their deficiency or excess, however, play a significant role in the pathogenesis and progression of numerous diseases, including those associated to metabolic syndrome. Literature reports confirm the possibility of toxic metals such as lead and cadmium to be involved in the development of diabetes [3][4][5][6][7]. Animal experiments confirmed that cadmium exposure results in impaired glucose tolerance by down-regulating GLUT-4 expression in adipocytes as well as necrosis and degeneration of pancreatic B cells, which impairs the synthesis and release of insulin [8,9].…”
Section: Discussionmentioning
confidence: 53%